Numerical analysis of mathematical model of nanofluid flow through stagnation point involving thermal radiation, activation energy, and living organisms - Munaza Chaudhry; Muhammad Abdul Basit; Muhammad Imran; Madeeha Tahir; Aiedh Mrisi Alharthi; Jihad Younis (AIP Advances)
In a stagnation point flow, the rate at which heat transfers in fluid containing nanoparticles across a sheet that is stretchable on a surface having pores has been investigated in this research. Magnetohydrodynamic viscous nanofluid flow is considered that is subjected to Brownian movements and the thermophoresis effect. By utilizing a numerical technique, the characteristics of heat transmission in nanofluids are investigated. The model is based on momentum, energy, and concentration equations. To explain the flow model’s physical significance, zero mass flux condition has been employed at the surface. Nonlinear partial differential equations are transformed into a collection of linked ordinary differential equations via similarity transformations. Convergent implications of nonlinear systems are produced by MATLAB software’s built-in bvp4c algorithm. To indicate the physical importance, a thorough examination of relevant characteristics, such as heat sink/source, porosity, and magnetic parameter is conducted. We have observed the behavior of profiles by fixing the numerical values of the involving parameters as 0.1 ≤ λ ≤ 2.0, 0.1 ≤ Nr ≤ 3.0, 0.1 ≤ R ≤ 0.4, 0.1 ≤ M ≤ 0.4, 0.1 ≤ Rb ≤ 1.5, and 0.1 ≤ Nb ≤ 0.7. The temperature rises yet the rate at which heat transfers at the surface declines due to the increased far-field velocity. The greater nanoparticles concentration at the far field relative to the surface is related to the zero mass flux condition.